Comparative Bioaccumulation of Heavy Metals (Fe, Zn, Cu, Cd, Cr, Pb) in Different Edible Mollusk Collected from the Estuary Area of Sarawak River - Nur Atiqah, Binti Mohammad Yusoff; Shabdin, Mohd Long (Universiti Malaysia Terengganu, 2011)
The tissue of mollusk such as Polymesoda expansa, Meretrix meretrix and Solen regularis are being relatively eaten by the local people as other marine organisms along the estuary of Sarawak River. The tissue samples and sediment samples were analyzed for heavy metals by using Atomic Absorption Spectrophotometer (AAS). The mean concentration of the heavy metals zinc (Zn) and copper (Cu) in selected mollusk species were below the permissible limit when compared with the Malaysian Food Act 1983 except for cadmium (Cd). The cadmium (Cd) concentration was exceeded the permissible limit. The bioaccumulation factor (BAFs) of Cd, Cu, Fe, Cr, Pb and Zn in whole tissue of Polymesoda expansa, Meretrix meretrix and Solen regularis in relative to mean metal concentrations in sediments was measured. The bioaccumulation factor (BAFs) results revealed the following descending order: Zn > Fe > Pb > Cr > Cd > Cu, (Polymesoda expansa), Fe > Cd > Cu > Pb> Zn > Cr (Meretrix meretrix) and Cu > Cr > Pb > Cd > Fe > Zn (Solen regularis).